Answer:
(b) -1 = i^(0+1+2+3+4)=i^(10) = (i^2)^5=(-1)^5 = -1.
Hope that helped :)
Step-by-step explanation:
Answer:
i⁰ × i¹ × i² × i³ × i⁴ = (−1)
Step-by-step explanation:
The imaginary unit is denoted by the symbol i and is equal to square root of −1. The square of the imaginary unit is equal to −1.
Therefore, i = √−1 and i² = −1
also i⁰ = 1
Now solving the given expression
i⁰ × i¹ × i² × i³ × i⁴
= 1 × i¹ × i² × i³ × i⁴
= i¹ × (i¹ × i¹) × (i¹ × i¹ × i¹) × (i¹ × i¹ × i¹ × i¹)
= i² × i² × i² × i² × i²
= (−1) ×(−1) ×(−1) ×(−1) ×(−1)
= (−1)